Genome-wide exploration of the GDSL-type esterase/lipase gene family in rapeseed reveals several BnGELP proteins active during early seedling development - Ding, Yahui; Xing, Liwen; Xu, Jiamin; Jiang, Teng; Tang, Xiuhua; Wang, Yaxuan; Huang, Shuhua; Hao, Wenfang; Zhou, Xiaona; Zhang, Yanfeng; Xie, Chang Gen (Frontiers in Plant Science, 2023)
The Gly-Asp-Ser-Leu (GDSL)-type esterase/lipase proteins (GELP) are one of the most important families of lipolytic enzymes and play prominent roles in seed germination and early seedling establishment through mobilizing the lipids stored in seeds. However, there are no comprehensive studies systematically investigating the GELP gene family in Brassica napus (BnGELP), and their biological significance to these physiological processes are far from understood. In the present study, a total of 240 BnGELP genes were identified in B. napus cultivar “Zhongshuang 11” (ZS11), which is nearly 2.3-fold more GELP genes than in Arabidopsis thaliana. The BnGELP genes clustered into 5 clades based on phylogenetic analysis. Ten BnGELPs were identified through zymogram analysis of esterase activity followed by mass spectrometry, among which five clustered into the clade 5. Gene and protein architecture, gene expression, and cis-element analyses of BnGELP genes in clade 5 suggested that they may play different roles in different tissues and in response to different abiotic stresses. BnGELP99 and BnGELP159 were slightly induced by cold, which may be attributed to two low-temperature responsive cis-acting regulatory elements present in their promoters. An increased activity of esterase isozymes by cold was also observed, which may reflect other cold inducible esterases/lipases in addition to the ten identified BnGELPs. This study provides a systemic view of the BnGELP gene family and offers a strategy for researchers to identify candidate esterase/lipase genes responsible for lipid mobilization during seed germination and early seedling establishment.